Long-term stability of cylindrical shells of viscoelastic composites - Sirius, Vaclovas (Lietuvos matematikos rinkinys, 2002)
On the grounds of Hamilton’s principle the system of linear integral equations has been obtained for the solution of stability problems of cylindrical shells made of viscoelastic composite materials by the finite element method.